The Principles of Islamic Communication on Reference Services at the Indonesian Trade Training Center Library - Hilya Maylaffayza; Prisinta Wanastri (Syarif Hidayatullah State Islamic University of Jakarta, INDONESIA, 2022)
Communication is the thing that can be separated from library activities. All library services rely on communication to interact with their users, especially reference services. Communication in reference services is personal, so the application of interpersonal communication skills must be owned by the reference librarian. Interpersonal communication is regulated and exemplified in Islam, with the Qur'an and Hadith. In the library environment, the principles of Islamic communication can certainly be applied by the librarian. This paper discusses applying Islamic communication principles to referral services at the Trade Training Center Library, Ministry of Trade of the Republic of Indonesia. The qualitative method with a case study approach is carried out in the research, where the data was collected by interviewing librarians and users in the library. This study shows that the librarian of the reference service to the users at the Library of the Trade Training Center of the Republic of Indonesia applies the principles of Islamic communication in interacting with users, which include: qaulan sadidan (speaking honestly), qaulan baligha (speaking clearly), qaulan ma'rufa (talking with wise), qaulan karma (speaking with noble words), qaulan layyina (speaking gently), and qaulan maysura (speaking politely). In addition, librarians are also able to uphold the principles of ukhuwah islamiyah (creating good relations with users), tabbayun (always cross-checking on developing information), and also fastabiqul khairat (inviting staff and users to compete for goodness).